1997
DOI: 10.1007/pl00006176
|View full text |Cite
|
Sign up to set email alerts
|

Analysis of Ribosomal RNA Genes Suggests That Trypanosomes Are Monophyletic

Abstract: To further investigate the phylogeny of protozoa from the order Kinetoplastida we have sequenced the small subunit (SSU) and a portion of the large subunit (LSU) nuclear rRNA genes. The SSU and LSU sequences were determined from a lizard trypanosome, Trypanosoma scelopori and a bodonid, Rhynchobodo sp., and the LSU sequences were determined from an insect trypanosomatid, Crithidia oncopelti, and a bodonid, Dimastigella trypaniformis. Contrary to previous results, in which trypanosomes were found to be paraphyl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
61
0
7

Year Published

1998
1998
2019
2019

Publication Types

Select...
6
2

Relationship

1
7

Authors

Journals

citations
Cited by 102 publications
(73 citation statements)
references
References 34 publications
5
61
0
7
Order By: Relevance
“…E-mail: j.r.stevens@ex.ac.uk 2000) and even in those parasites of medical importance, it is little more than a decade since the widespread introduction of DNA sequencing technologies has allowed the evolution of parasitic trypanosomatids (and kinetoplastids in general) to be evaluated by formal phylogenetic analysis (Fernandes et al, 1993;Alvarez et al, 1996;Maslov et al, 1996;Lukes et al, 1997;Haag et al, 1998;Hannaert et al, 1998;Stevens et al, 1999Stevens et al, , 2001Wright et al, 1999;Hamilton et al, 2004;Moreira et al, 2004). To fully understand the evolutionary history of parasitic kinetoplastids and to understand the context within which the evolution of each parasite group has unfolded, an understanding not just of the parasites, but also of broader kinetoplastid phylogenetics is required.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…E-mail: j.r.stevens@ex.ac.uk 2000) and even in those parasites of medical importance, it is little more than a decade since the widespread introduction of DNA sequencing technologies has allowed the evolution of parasitic trypanosomatids (and kinetoplastids in general) to be evaluated by formal phylogenetic analysis (Fernandes et al, 1993;Alvarez et al, 1996;Maslov et al, 1996;Lukes et al, 1997;Haag et al, 1998;Hannaert et al, 1998;Stevens et al, 1999Stevens et al, , 2001Wright et al, 1999;Hamilton et al, 2004;Moreira et al, 2004). To fully understand the evolutionary history of parasitic kinetoplastids and to understand the context within which the evolution of each parasite group has unfolded, an understanding not just of the parasites, but also of broader kinetoplastid phylogenetics is required.…”
Section: Discussionmentioning
confidence: 99%
“…A monophyletic group consists of taxa that are descended from a single common ancestor and contains all known descendants from that ancestor. The first molecular phylogenetic studies, based on comparisons of mitochondrial and nuclear ribosomal DNAs (rDNA), showed trypanosomes to be paraphyletic (Gomez et al, 1991;Fernandes et al, 1993;Maslov et al, 1996), while subsequent rDNA-based studies, which have included more taxa from a far broader range of host species (Lukes et al, 1997;Stevens et al, 1999Stevens et al, , 2001Wright et al, 1999;Simpson et al, 2002;Hamilton et al, 2004) (Fig. 2) supported monophyly.…”
mentioning
confidence: 99%
“…The ssu rRNA gene has become the marker of choice for evolutionary analyses of the kinetoplastid protozoa (e.g. Fernandes et al 1993, Maslov et al 1994, Marché et al 1995, Lukes et al 1997, Haag et al 1998.…”
Section: Methodsmentioning
confidence: 99%
“…However, it is only recently, with advances in molecular and phylogenetic methods, that significant progress towards resolving trypanosome evolutionary history is being made (e.g. Lake et al 1988, Fernandes et al 1993, Wiemer et al 1995, Maslov et al 1996, Lukes et al 1997, Haag et al 1998.…”
mentioning
confidence: 99%
“…Fernandes et al (1993), Maslov et al (1996) and Lukes et al (1997) utilised variation within the 18S to infer phylogeny within the kinetoplatids leading to the suggestion that Trypanosoma was monophyletic. Noyes (1998) expanded upon the taxonomic coverage of the 18S data and stimulated much debate both in biogeographic implications (Stevens & Gibson 1998) and methodology of inference from these data (Maslov & Lukes 1998, Noyes & Rambaut 1998.…”
Section: Refined Homologiesmentioning
confidence: 99%